Combined effects of drought and soil fertility on the synthesis of vitamins in green leafy vegetables - Park, Taewan; Fischer, Sahrah; Lambert, Christine; Hilger, Thomas; Jordan, Irmgard; Cadisch, Georg (MDPI, 2023)
Green leafy vegetables, such as Vigna unguiculata, Brassica oleraceae, and Solanum scabrum, are important sources of vitamins A, B1, and C. Although vitamin deficiencies considerably affect human health, not much is known about the effects of changing soil and climate conditions on vegetable vitamin concentrations. The effects of high or low soil fertility and three drought intensities (75%, 50%, and 25% pot capacity) on three plant species were analysed (n = 48 pots) in a greenhouse trial. The fresh yield was reduced in all the vegetables as a result of lower soil fertility during a severe drought. The vitamin concentrations increased with increasing drought stress in some species. Regardless, the total vitamin yields showed a net decrease due to the significant biomass loss. Changes in vitamin concentrations as a result of a degrading environment and increasing climate change events are an important factor to be considered for food composition calculations and nutrient balances, particularly due to the consequences on human health, and should therefore be considered in agricultural trials.